AB0896 Performances of spondyloarthritis (SPA) sets of criteria for diagnostic and classification purposes in patients visiting a rheumatologist because of chronic back pain: The declic study. (23rd January 2014) - Dougados, M.; Paternotte, S.; Comet, D.; Hacquard-Bouder, C.; Rudwaleit, M.; Claudepierre, P.; van der Heijde, D.
Abstract : Background: The main difference in the different sets of criteria for axial SpA (e.g. mNY, Amor, ESSG and more recently ASAS) is based on the requirement of sacro-iliac damage in the conventional mNY criteria. Objectives: To evaluate in rheumatological daily practice the performances of the different sets of axial SpA criteria either at the time of the diagnosis (diagnostic purpose) or at the time of the study (classification purpose). Methods: Study design: cross-sectional, multi-centre. Patients: chronic back pain which has occurred before the age of 45 years visiting a rheumatologist in France. Data collected: a) the items included in the different sets of criteria checking whether they were present at the time of the diagnosis or at the time of the study visit; b) the diagnosis of the rheumatologist at the time of the study visit. Statistical analysis: rheumatologist's diagnosis was considered as the ``gold standard"; the absence of information was considered as ``normal" or ``absent" in the evaluation of the performances ( e.g. Se, Spe) of the different sets of criteria. Results: Of the 1379 recruited patients, 1212 patients had a definite diagnosis, 785 (64.8%) were suffering from non-SpA diseases ( e.g. ``controls", mainly mechanical back disorders n=728) and 427 (35.2%) were diagnosed as SpA (ankylosing spondylitis =306, psoriatic arthritis =48, IBD related arthritis =17, reactive arthritis =4, undifferentiated SpA =52). An axial SpA ( e.g. ``study disease") was diagnosed in 419 (34.6%). Patients characteristics in the axial SpA versus controls, respectively were: age 38.8±10.0 versus 44.2±11.3 years, female sex: 181 (43.2%) versus 375 (47.8%), disease duration: 7.6±6.1 versus 7.6±6.4 years. The table summarizes the performances of the different sets of criteria. Radiological sacro-iliitis was observed in 41%, 48% and 67% of the 419 axial SpA with axial symptoms duration less than 5, less than 10 and more than 10 years respectively. Conclusions: These data suggest that a) the prevalence of SpA in patients suffering from chronic low back pain before the age of 45 and visiting a rheumatologist is high; b) The performances of the different sets of SpA are acceptable and better than the ones of ankylosing spondylitis ( e.g. m NY) at both the time of presentation of the patient to a rheumatologist (diagnostic purpose) and at the time of a further visit (classification purpose) suggesting that a structural damage of the sacro-iliac joints is not occurring systematically in the natural course of the disease Disclosure of Interest: M. Dougados Grant/Research support from: Abbott Ltd France, S. Paternotte: None Declared, D. Comet: None Declared, C. Hacquard-Bouder: None Declared, M. Rudwaleit: None Declared, P. Claudepierre: None Declared, D. Van der Heijde: None Declared